Strength and durability studies on ficus exasperata leaf ash concrete. (2021) - Elango, K.S.; Remya, P.R.; Vivek, D.; Gopi, R.; Rajeshkumar, V.; Saravanakumar, R.
Abstract: This paper deals with the feasibility of using Ficus Exasperata Leaf Ash (FELA) as a partial substitute to cement. Ordinary Portland Cement (OPC) was replaced with FELA. The replacement percentage varied from 10% to 30% with uniform increment of 5%. The physical and durability properties were studied to identify the performance of concrete when partially replaced with FELA instead of cement. The grade of concrete used in this study is M25 so that it produces the characteristic compressive strength of 25 MPa. Moreover SEM and XRD studies have been carried out to study the microstructural properties of FELA concrete. The results were arrived and discussed elaborately. From the experimental investigation, it was clearly observed that 15% replacement of FELA in cement showed promising strength and durability properties when compare to other percentage replacement and it was considered as the optimum one.